2011
DOI: 10.1517/14712598.2011.585152
|View full text |Cite
|
Sign up to set email alerts
|

Targeted biological therapies for pain

Abstract: Biological therapy of pain holds great promise and is rapidly developing. Despite the significant numbers of preclinical studies in the last two decades only a single biological agent, the cone snail toxin ziconotide, has been advanced through all stages and licensed for clinical use. Biological therapy of pain is thus here to stay, but will need more substantial proof of efficacy and safety before being widely accepted and routinely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Chronic and neuropathic pain can adversely affect a patient's overall health‐related quality of life [1–4], including physical and emotional functioning, and is associated with substantial societal costs [5–7]. Chronic pain is challenging to manage, and many patients have pain that is refractory to existing treatments [6,8–10]. Numerous randomized clinical trials have shown that no more than half of patients experience clinically relevant pain relief, which is almost always partial but not complete.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic and neuropathic pain can adversely affect a patient's overall health‐related quality of life [1–4], including physical and emotional functioning, and is associated with substantial societal costs [5–7]. Chronic pain is challenging to manage, and many patients have pain that is refractory to existing treatments [6,8–10]. Numerous randomized clinical trials have shown that no more than half of patients experience clinically relevant pain relief, which is almost always partial but not complete.…”
Section: Introductionmentioning
confidence: 99%
“…We know that changes in peripheral joint innervation are partly responsible for degenerative alterations in joint tissues which contribute to the development of OA [32,33]. This is why targeting NGF and peripheral innervation in painful arthritic joints with targeted biological drugs is timely and important [34][35][36]. Ion channels and G-protein coupled receptors (which are often ion channels themselves) in peripheral innervation of painful osteoarthritis joints must therefore be a high priority target for therapeutic monoclonal antibodies (mAbs) and biological drugs that are administered intra-articularly rather than injected subcutaneously or systemically [37][38][39][40].…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%